Powinności w perspektywie zasad współżycia społecznego. - Pietrzykowski, Krzysztof (Kwartalnik Prawa Publicznego, 2016)
The clause defining “the rules of social coexistence”, which first appeared in Poland in 1950, despite systemic changes is still contained in many Polish legal acts. Its meaning, however, has been transformed. At the same time, the process of replacing the rules of social coexistence with other general clauses, especially for reasons of equity and good morals, is under way. In contemporary jurisprudence of the Supreme Court prevails the view that the clause of social coexistence consists essentially of referring to the principles of equity, good faith in the objective sense or the principles of fairness in civil law. This case law also points to the basic duty of the addressees of the clause of the principles of social coexistence, manifested in ethical and fair conduct consistent with the principles of equity and good faith in the objective sense. In the literature, however, it is emphasized that the principles of social coexistence are, by nature, an objective concept, and there is a number of rules defining the scope of application of the provisions referring to this concept (especially Art. 5 of the Civil Code), which aim to further objectivize the measures contained in these provisions. One should mention here, above all, the fact that the principles of social coexistence should be treated as an immanent factor of all behavior, and the content of Art. 5 of the Civil Code should be taken into account when ruling each case. The principles of social coexistence are undoubtedly a source of non-normative duties, directly linked with the strict prohibition to violate these principles.